A Preliminary Study on Insect Pollinators of New Forest Campus, Dehradun, India - Kumar, Arvind; Lakshamikanta Panda, L.R.; Ray, Aishwarya (Indian Forester, 2022)
The present study was undertaken to find out the insect pollinators associated with some plants in the New Forest Campus, FRI, Dehradun, India. The observations were taken by three different methods from April to July 2020. The study revealed that 45 insect pollinator species belonging to four orders and ten families were present in the campus. A total of 32 flowering plant species were observed to be visited by 45 insect pollinators among them species richness of butterflies was maximum followed by non apis bees, apis bees, wasps and syrphidflies, but bees were the most dominated species for pollination in the campus. Among the host plants flowers of Peltophorum pterocarpum was visited by maximum number of pollinators (11 species), followed by Lantana camara (8 species), Lichi chinensis (6 species), Bidens alba (4 species) and Mangifera indica (3 species), etc.